Developing and validating a multivariable prediction model to improve the diagnostic accuracy in determination of cervical versus endometrial origin of uterine adenocarcinomas: A prospective MR study combining diffusion‐weighted imaging and spectroscopy. Issue 6 (27th November 2017) - Lin, Gigin; Lin, Yu‐Chun; Wu, Ren‐Chin; Yang, Lan‐Yan; Lu, Hsin‐Ying; Tsai, Shang‐Yueh; Huang, Yu‐Ting; Huang, Yen‐Ling; Lu, Kuan‐Ying; Ng, Koon‐Kwan; Yen, Tzu‐Chen; Chao, Angel; et al.
Abstract : Background: A triage test to assist clinical decision‐making on choosing primary chemoradiation for cervical carcinomas or primary surgery for endometrial carcinomas is important. Purpose or Hypothesis: To develop and validate a multiparametric prediction model based on MR imaging and spectroscopy in distinguishing adenocarcinomas of uterine cervical or endometrial origin. Study Type: Prospective diagnostic accuracy study. Population: Eighty‐seven women: 25 cervical and 62 endometrial adenocarcinomas divided into training (n = 43; cervical/endometrial adenocarcinomas = 11/32) and validation (n = 44; 14/30) datasets. Field Strength/Sequence: The 3T diffusion‐weighted (DW) MR imaging and MR spectroscopy. Assessment: Morphology, volumetric DW MR imaging and spectroscopy (MDS) scoring system with total points 0–5, based on presence of the following MR features assessed independently by two radiologists: (a) epicenter at the cervix, (b) rim enhancement, (c) disrupted cervical stromal integrity, (d) mean volumetric apparent diffusion coefficient values (ADCmean) higher than 0.98 × 10‐3 mm 2 /s, (e) fatty acyl δ 1.3 ppm more than 161.92 mM. Histopathology as gold standard. Statistical Tests: Logistic regression and receiver operator characteristic (ROC) curves analysis. Results: For both the training and validation datasets, the MDS score achieved an accuracy of 93.0% and 84.1%, significantly higher than that of morphology (88.4% and 79.5%), ADC value (74.4% and 68.2%), and spectroscopy (81.4% and 68.2%; P < 0.05 for all). The performances of the scoring were superior to the morphology in the training dataset (areas under the receiver operating characteristics curve [AUC] = 0.95 vs. 0.89; P = 0.046), but not in the validation dataset (AUC = 0.90 vs. 0.85; P = 0.289). Data Conclusion: MDS score has potentials to improve distinguishing adenocarcinomas of cervical or endometrial origin, and warrants large‐scale studies for further validation. Level of Evidence: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:1654–1666.